CHILD MALTREATMENT AND DEPRESSION: THE ROLE OF SOCIAL SUPPORT - Azimi, Andia (2018)
The goal of the current study is to examine the differential mediating and moderating effects of social support on depression after experiencing child maltreatment. The differential effects of social support will be examined by source and type of social support. Differences across gender will also be examined.It is expected that experiencing child maltreatment will increase the probability of depression, but social support in general is expected to mediate and moderate the relationship between maltreatment and depression. Emotional social support, especially from family, is expected to have the largest mediating effect on mental health outcomes among maltreatment victims compared (Cohen & Willis, 1985; Thoits, 1995). To investigate these relationships, data are used from the National Longitudinal Study of Adolescent to Adult Health (Add Health). Structural equation modeling will be used to analyze the hypotheses. Directions for future research and policy implications will be discussed